STUDY ON IMPROVING THE QUALITY OF DRIVING SKILL BY SIXTH GRADE STUDENTS - Gheorghe Gabriel CUCUI; Ionela Alina CUCUI (Cluj University Press, 2017)
Quality motric skill has a complex content because of the relationship they have with other driving qualities and the skills and driving skills. Any voluntary motric action, regardless of the degree of difficulty to be performed requires a certain level of skill and some coordination at the level of the cerebral cortex. The topic discussed is current being the object of study for many specialists of this domain thanks to its importance in getting the performance at any level. Starting from the premise that the sports activity becomes component of daily activities, practicing base appropriation physical exercise are in the organized framework. In the educational process increasingly requesting physical education lesson creative thinking of students, so as to build their capacity to operate with driving actions learned and apply appropriate measures in certain driving situations. Learning and applying skills and driving skills in practice broaden the horizons of knowledge of students from point of view motric. Students become more skilled, more agile and more resistant to easily resolve difficulties that arise in practice. Motor basic education in general and particularly Aimed at skill development of school tasks not so immediate, and especially Subsequent Their use in diversity activities. REZUMAT. Studiu privind îmbunătățirea îndemânării la elevii de clasa a VI-a. Îndemânarea este o calitate motrică complexă, având profunde interferențe atât cu celelalte calități motrice, cât și cu priceperile și deprinderile motrice. Orice acțiune motrică voluntară, indiferent de gradul de dificultate, pentru a putea fi efectuată necesită un anumit nivel de îndemânare și o anumită coordonare la nivelul scoarței cerebrale. Tema abordată este de actualitate fiind obiect de studiu pentru mulți specialiști ai domeniului datorită importanței ei în obținerea performanțelor la orice nivel. Plecând de la premisa că activitatea sportivă devine componentă a activității cotidiene, baza însușirii practicării exercițiului fizic se află în cadru organizat. În procesul instructiv-educativ lecția de educație fizică solicită permanent gândirea creatoare a elevilor, în așa fel încât să le formeze acestora capacitatea de a opera cu acțiunile motrice însușite și de a aplica acte motrice potrivite în anumite situații concrete. Învățarea și aplicarea deprinderilor și priceperilor motrice în practică lărgește orizontul cunoașterii al elevilor din punct de vedere motric. Elevii devin mai îndemânatici, mai agili și mai rezistenți în rezolvarea cu ușurință a dificultăților ce apar în activitatea practică. Educarea calităților motrice de bază în general și a îndemânării în special vizează nu atât realizarea unor sarcini școlare imediate, cât mai ales utilizarea lor în diversitatea activităților ulterioare. Cuvinte cheie: dezvoltare, gimnaziu, îndemânare.